Identification Of The Factors Affecting The Motivational Level Of Primary School Teachers In Tehsil Pindibhatian, District Hafizabad - Fasih-ur-Rehman fasih; Fiaz Ahmad Fiaz; Rizwan Ahmad (International Journal of Technology and Education Research, 2023)
This study was designed to examine the factors affecting motivational level of primary school teachers were in tehsil Pindibhatian. Major objectives of the study was to identify the factors responsible for the motivation of The aim of this study was to explore teachers were ’ motivational aspects in the education process. The total numbers of male primary schools in tehsil Pindi Bhattian are 157 and 592 male teachers were are appointed in these schools. Due to the time and resources availability forty (40) schools was selected purposely and three (3) teachers were was selected from each school. So, the number of respondents is 120 teachers using purposive sampling technique. This study was descriptive in nature and for data were collection well structure questionnaire was used. Data were analyzed trough statistical package for social sciences (SPSS). Results of the study showed thatless than half of the respondents were between 31-35 age. Majority of the respondents belonged to urban area. More than one third of the respondents were master. Half of the respondents were having B.Ed. Almost all respondents were agree with the statements that in-service training, financial factors, behavior of head teachers were the major factors that effects the job performance of teachers.